An Examination of the Ethical Issues Facing Agricultural Communicators in Seven Agricultural Communication Organizations - Shawn L. Oliver; Curtis Paulson (Journal of Applied Communications, 1995)
The purpose of this study was to explore and describe the ethical issues facing agricultural communicators. Members of seven agricultural communication professional organizations, including AAEA, ACE, ARC, CCA, LPC, NAAJ, and NAFB were surveyed and asked to respond to 51 statements based on whether they felt each statement was an ethical issue facing agricultural communicators. Twelve major, ethical issues rose to the top of the list. The results also showed major ethical issues facing agricultural communicators as recognized by each organization. A factor analysis identified four factors which influenced how the agricultural communicators evaluated the ethical issues.